THE DYNAMICS OF LANGUAGE ATTITUDES OF THE TEENAGERS AT DESA BUDUK, BADUNG TO BALINESE LANGUAGE - I Nyoman Muliana; Subur Made; Suarjaya Anak Agung Gede (KULTURISTIK: Jurnal Bahasa dan Budaya, 2021)
This research has the background of the phenomena of local languages claimed to decrease in numbers these decades. It aims to explore the dynamics of language attitudes of the teenagers at Desa Buduk, Badung and the factors causing the dynamics supported by using theory of Language Attitudes of Ladegaard (2000). The methods applied in this research included survey and participative observation. The results of the research show that the language attitudes of the teenagers to Balinese language are dynamic. The quantitative analysis indicates that 80% of them strongly agreed to the statements of cognitive language attitudes about Balinese language and its speakers. Then, 80% of them also agreed to the statements of affective language attitudes language concerning with preference in using Balinese language, but they disagreed the statements of greetings using other language than Balinese language and news on TVs and radios using other language than Balinese language and news. They also had positive for the statement in conative language attitudes concerning with the transfer of Balinese language to their children, but in that component of language attitude they were negative for statements about responses of using Balinese language only, admonishing people using other language, and switching off TV or radio using languages other than Balinese. The qualitative analysis of this research shows that most teenagers at Desa Buduk, Badung had positive language attitudes to Balinese language indicated by their behaviors using Balinese language. But, some high class teenagers showed the use of Indonesian language. The dynamics of the language attitudes of the teenagers at Desa Buduk, Badung to Balinese language by language loyalty, language value, and residential density.